The development of the tort of passing-off - Lilienthal, Gary I. (Curtin University, 2012)
This thesis investigates the historical development of the tort of passing-off. Morison said that the term “passing off” indicates the act of offering goods for sale with an accompanying misrepresentation, either by words or by conduct as to the origin of the goods, whereby the purchaser has been misled and business has been diverted from the plaintiff to the defendant.1 It is called a strict liability tort because the plaintiff does not need to show any wrongful intention on the part of the defendant, fraud apparently having been abandoned as an element for proof in the tort of passing-off.The composite research question of the thesis is in two parts, as follows: ‘Has the historical development of the tort of passing off resulted in the tort becoming a strict liability tort? If so, why and how did this development take place?'The tort of passing-off derives from the direct rule by the English Kings of earlier times, and was developed both as a general regulatory instrument to control industry, and in particular to make industry more war-ready.2 The tort of passing-off has a very substantial history in the jurisprudence of the medieval and late middle ages craft gilds and counties of the United Kingdom. The purpose of this thesis is to set out how the tort developed from the ordinances of gild and county jurisprudence into the royal courts, and to see whether, why and how from that form of development it developed as a strict liability tort.